Pelatihan Pemanfaatan Media Pembelajaran Sistem Kontrol Berbasis Elektro Pneumatik Di SMKN 9 Makassar - Muchtar, Akhyar; Muhammad Iswal Burhan; Dessy Ana Laila Sari; Elfira Makmur; Hilda Ashari (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
The use of electro-pneumatic learning media at SMKN 9 Makassar holds great potential to enhance students' understanding in the field of electrical engineering. However, teachers at the school have not yet been able to fully utilize this media, primarily due to limited technical knowledge. Although electro-pneumatic devices are available at the school, only a few teachers are capable of operating them independently, resulting in minimal use of this technology in teaching and learning activities. Through this community service initiative, these challenges faced by teachers are addressed through systematic training that includes both theoretical instruction and hands-on practice. The training is conducted in several stages, from field orientation to demonstration and simulation, enabling teachers not only to familiarize themselves with electro-pneumatic technology but also to apply it in daily classroom teaching. This training aims to increase teacher professionalism and effectively utilize electro-pneumatic media to create an interactive and practical learning environment.